MRI-guided adaptive radiotherapy for prostate cancer: When do we need to account for intra-fraction motion?. (November 2022) - Lawes, R.; Barnes, H.; Herbert, T.; Mitchell, A.; Nill, S.; Oelfke, U.; Pathmanathan, A.; Smith, G. Adair; Sritharan, K.; Tree, A.; McNair, H.A.; Dunlop, A.
Highlights: Visualising that the prostate is within the PTV is an effective decision making process. The dose calculated on the image immediately prior to delivery can be used to quantify the decision process. Abstract: A shift of the daily plan can mitigate target position changes that occur between daily MR acquisition and treatment for MR-linac radiotherapy, but increases the session time. We demonstrated that our workflow strategy and decision-making process, to determine whether a subsequent shift is necessary, is appropriate.